CGRP Reduces Apoptosis of DRG Cells Induced by High-Glucose Oxidative Stress Injury through PI3K/AKT Induction of Heme Oxygenase-1 and Nrf-2 Expression. (25th November 2019) - Liu, YaDong; Zhang, SiCong; Xue, Jun; Wei, ZhongQing; Ao, Ping; Shen, BaiXin; Ding, LiuCheng
Abstract : Dorsal root ganglion (DRG) neurons, which are sensitive to oxidative stress due to their anatomical and structural characteristics, play a complex role in the initiation and progression of diabetic bladder neuropathy. We investigated the hypothesis that the antioxidant and antiapoptotic effects of CGRP may be partly related to the expression of Nrf2 and HO-1, via the phosphatidylinositol 3-kinase (PI3K)/AKT pathway, thus reducing apoptosis and oxidative stress responses. This study shows that CGRP activates the PI3K/AKT pathway, thereby inducing increased expression of Nrf2 and HO-1 and resulting in the decrease of reactive oxygen species and malondialdehyde levels and reduced neuronal apoptosis. These effects were suppressed by LY294002, an inhibitor of the PI3K/AKT pathway. Therefore, regulation of Nrf2 and HO-1 expression by the PI3K/AKT pathway plays an important role in the regulation of the antioxidant and antiapoptotic responses in DRG cells in a high-glucose culture model.